Mutation in the 26S proteasome regulatory subunit rpn2 gene in Plasmodium falciparum confers resistance to artemisinin. - Gonçalves, Adriana F. (2024)
The author(s) declare financial support was received for the research, authorship, and/or publication of this article. Financial support was provided by grants from Portuguese National funds, through the Foundation for Science and Technology (FCT) -project UIDB/50026/2020 (DOI 10.54499/UIDB/50026/2020), UIDP/50026/2020 (DOI 10.54499/UIDP/50026/2020) and LA/P/0050/2020 (DOI 10.54499/LA/P/0050/2020), PTDC/SAU-PAR/2766/2021 to PF and 2022.12892.BD to AG. Copyright © 2024 Gonçalves, Lima-Pinheiro, Teixeira, Cassiano, Cravo and Ferreira.